Improving Surgical Capacity and Infection Prevention in Resource-Limited Settings: A Case Study of Kyrgyzstan - Niyazova Salima, Mamakeev Kanat, Niyazov Batyrkhan, Mamakeev Mambet, Ashimov Zhanybek, Yethindra Vityala, (Asian Journal of Pharmaceutics (AJP), 2025)
Post-graduate surgical training programs in low- and middle-income countries (LMICs) face challenges such as limited resources, high infectious disease rates, and poor infection prevention and control (IPC) measures. A review of surgical education in 34 LMICs, particularly Kyrgyzstan, identified these obstacles, assessed IPC practices, and suggested improvements. Despite local adaptations, LMICs struggle with trainer shortages, balancing clinical and educational demands, and inadequate healthcare funding. The link between surgical education and infection management is critical in LMICs because of the higher communicable disease rates and increased surgical risks. Recommended strategies include integrating IPC education into surgical curricula, upgrading sterilization and personal protective equipment, and developing IPC policies, community involvement, and research to guide interventions. The Kyrgyz State Medical Institute and National Surgical Center case study highlighted the importance of collaboration, organizational structures, and regulatory frameworks in enhancing surgical training and healthcare outcomes. Addressing these issues requires infrastructure improvements, policy implementation, community engagement, and international collaboration, with progress monitored using metrics such as surgical workforce density, surgical volume, and perioperative mortality rates.